Telemedizin, Herzinsuffizienz und der ewige Glaube an die Technik: Eine konstruktive hausärztliche Analyse und Kritik ihrer Einführung in Deutschland - Kühlein, Thomas; Roos, Marco; Beier, Markus; Eggenwirth, Peter; Engel, Bettina; Scherer, Martin (Zeitschrift für Allgemeinmedizin, 2023)
Background: Patients with the diagnosis heart failure are frequently frail and have a poor prognosis. Now medicine is confronting them with new digital technology in the form of telemedicine with the aim of a never-ending prolongation of live, in smaller and smaller amounts. Objectives: Evaluation of the introduction of telemedicine for patients with heart failure from the perspective of primary care. Materials and methods: Summary of the scientific and non-scientific literature of the topic in a narrative review. Results: The evidence of telemedicine for heart failure is very extensive and heterogeneous. The benefit is hard to assess. The scientific basis of its introduction in Germany was reduced to a few studies which seem insufficient as a justification for it. Conclusion: An uncritical belief in technology combined with a political will based on it seems to be the real driver of this introduction. Instead of dissipating resources with more and more technology in ever smaller areas, the digitally assisted improvement of documentation and communication between patients and their primary care providers and in turn the telemedical connection and support of these by specialists might be the more appropriate answer.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cardiology; Continuity of patient care; Politics; Primary care; Telemonitoring